Analysis of the Roles and Capabilities of the Indonesian National Armed Forces in Response to the COVID-19 Pandemic as a Non-Military Threat - Heri Wiranto; Muhadjir Muhammad Darwin; Agus Heruanto Hadna; Djokosantoso Moeljono (GoAcademica Research & Publishing, 2023)
The spread of COVID-19 has been declared a non-natural national disaster, and it is recognized as a genuine non-military threat that necessitates collaboration among various institutions, particularly within the context of non-military defense, which falls under the purview of the Indonesian National Armed Forces (TNI). Responding to COVID-19 falls under the government’s responsibility, which includes the establishment of the COVID-19 Response Acceleration Task Force. The collaboration between civilian institutions and the TNI as elements of the unit is expected to demonstrate a streamlined and effective command line, aiming to uphold and safeguard the nation’s security effectively. This paper aims to analyze the role and capacity of TNI in addressing the COVID-19 Pandemic as a non-military threat by measuring the impact of various determinants on the implementation of the role and capabilities of TNI. The research employed a mixed methods approach, incorporating both sequential and concurrent models. Additionally, it involved an in-depth qualitative analysis of each determinant utilized in handling the COVID-19 pandemic. Generally, the primary elements in the COVID-19 Response Acceleration Task Force are civilian institutions based on the category of disaster and its societal impact. Nevertheless, the involvement of TNI through Military Operations Other Than War (OMSP) can expedite COVID-19 management through aid and humanitarian operations. Non-military defense operations strategically establish control command between ministries/agencies and local governments. The optimization of TNI’s capabilities in crisis management involves deploying personnel across Indonesia, with a central command under the TNI Commander and the establishment of command centers in crisis-affected areas. The success of TNI’s performance can be evaluated by examining its strategic leadership and patterns of civil-military cooperation in a systematic and deliberate manner.